Anticancer potential of β-sitosterol and oleanolic acid as through inhibition of human estrogenic 17beta-hydroxysteroid dehydrogenase type-1 based on an in silico approach. Issue 31 (13th July 2022) - Kristanti, Alfinda Novi; Aminah, Nanik Siti; Siswanto, Imam; Manuhara, Yosephine Sri Wulan; Abdjan, Muhammad Ikhlas; Wardana, Andika Pramudya; Aung, Ei Ei; Takaya, Yoshiaki
Abstract : We presented pharmacokinetic study, molecular docking, and MD simulation to study β-sitosterol and oleanolic acid compounds and potential HSD17B1 inhibitors. Abstract : The human estrogenic enzyme 17beta-hydroxysteroid dehydrogenase type-1 (HSD17B1) provides biosynthesis regulation of active estrogen in stimulating the development of breast cancer through cell proliferation. The β-sitosterol is classified as a steroid compound and is actually a type of triterpenoid compound that has a similar structure to a steroid. This similarity provides a great opportunity for the inhibitor candidate to bind to the HDS17B1 enzyme because of the template similarity on the active site. Several in silico approaches have been applied in this study to examine the potential of these two inhibitor candidates. Pharmacokinetic studies showed positive results by meeting several drug candidate criteria, such as drug-likeness, bioavailability, and ADMET properties. A combination of molecular docking and MD simulation showed good conformational interaction of the inhibitors and HSD17B1. Prediction of binding free energy (Δ G bind ) using the Molecular Mechanics-Generalized Born Surface Area (MM-GBSA) approach shows Δ G bind (kcal mol −1 ) of C1–HSD17B1: −49.31 ± 0.23 and C2–HSD17B1: −33.54 ± 0.34. Meanwhile, decomposition energy analysis (Δ G residuebind) suggested several key residues that were also responsible for the interaction with inhibitors, such as C1–HSD17B1 (six residues: Leu96, Leu149, Pro187, Met193, Val225, and Phe226) and C2–HSD17B1 (four residues: Ile14, Gly94, Pro187, and Val188). Hopefully, the obtained results from this research could be considered for the mechanistic inhibition of the HSDS17B1 enzyme at molecular and atomistic levels.